2023
DOI: 10.3892/etm.2023.11920
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase and aspartate aminotransferase levels associated with the severity of COVID‑19: A systematic review and meta‑analysis

Abstract: Lactate dehydrogenase (LDH) and aspartate aminotransferase (AST) are important indicators of cardiovascular, muscle and liver lesions, and can be used as prognostic indicators for infectious diseases, such as coronavirus disease 2019 . The present systematic review and meta-analysis assessed the prognostic value of LDH and AST levels for COVID-19 severity. Ovid-Medline, PubMed, Embase and The Cochrane Library were used to search for articles, according to the inclusion and exclusion criteria, until July 2022. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Many biological factors have been reported to be associated with COVID-19 clinical presentation. Although it was not its main hypothesis, in the present study, we observed older age, higher frequency of low oximetry and death; higher counts of NEUT and higher values of glucose, LDH, CXCL9 and CXCL10 chemokines, as well as lower LYMPH and PLT counts associated with COVID-19 severity (Table 1), corroborating previous reports relating these clinical and laboratory parameters with the disease (Abdollahzadeh et al, 2021;Apaydin et al, 2022;He et al, 2023;Ochoa-Ramírez et al, 2022;Zhang et al, 2023).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Many biological factors have been reported to be associated with COVID-19 clinical presentation. Although it was not its main hypothesis, in the present study, we observed older age, higher frequency of low oximetry and death; higher counts of NEUT and higher values of glucose, LDH, CXCL9 and CXCL10 chemokines, as well as lower LYMPH and PLT counts associated with COVID-19 severity (Table 1), corroborating previous reports relating these clinical and laboratory parameters with the disease (Abdollahzadeh et al, 2021;Apaydin et al, 2022;He et al, 2023;Ochoa-Ramírez et al, 2022;Zhang et al, 2023).…”
Section: Discussionsupporting
confidence: 92%
“…Concerning the laboratory parameters, they did not show differences among the different genotypes or alleles of VDR SNPs with the exception of FokI T allele which was associated with higher AST levels (Table 5). This might offer some clue in elucidating how this allele might contribute to COVID-19 pathology, taking into consideration that elevated AST values have been related to the severe forms (He et al, 2023).…”
Section: Discussionmentioning
confidence: 99%